Disparities in all-cause mortality among people experiencing homelessness in Toronto, Canada during the COVID-19 pandemic: a cohort study - Richard, Lucie; Carter, Brooke; Wu, Linda; Hwang, Stephen W. (Frontiers in Public Health, 2024)
People experiencing homelessness have historically had high mortality rates compared to housed individuals in Canada, a trend believed to have become exacerbated during the COVID-19 pandemic. In this matched cohort study conducted in Toronto, Canada, we investigated all-cause mortality over a one-year period by following a random sample of people experiencing homelessness (n=640) alongside matched housed (n=6,400) and low-income housed (n=6,400) controls. Matching criteria included age, sex-assigned-at-birth, and Charlson comorbidity index. Data were sourced from the Ku-gaa-gii pimitizi-win cohort study and administrative databases from ICES. People experiencing homelessness had 2.7 deaths/100 person-years, compared to 0.7/100 person-years in both matched control groups, representing an all-cause mortality unadjusted hazard ratio (uHR) of 3.7 (95% CI, 2.1-6.5). Younger homeless individuals had much higher uHRs than older groups (ages 25-44 years uHR 16.8 [95% CI 4.0-70.2]; ages 45-64 uHR 6.8 [95% CI 3.0-15.1]; ages 65+ uHR 0.35 [95% CI 0.1-2.6]). Homeless participants who died were, on average, 17 years younger than controls. After adjusting for number of comorbidities and presence of mental health or substance use disorder, people experiencing homelessness still had more than twice the hazard of death (aHR 2.2 [95% CI 1.2-4.0]). Homelessness is an important risk factor for mortality; interventions to address this health disparity, such as increased focus on homelessness prevention, are urgently needed.